2018
DOI: 10.4085/1062-6050-127-17
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Baths, Intramuscular Hemodynamics, and Oxygenation as Monitored by Near-Infrared Spectroscopy

Abstract: Application of CB induced a transient change in the hemodynamics and oxygenation of the gastrocnemius muscle in healthy individuals. The effect of CB application in improving tissue hemodynamics and oxygenation may, therefore, support the therapeutic benefits of CB in the treatment of muscle injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…This therapy helps reduce pain in upper and lower extremities, edema and inflammation of soft tissue, muscle spasm, and subacute phases stiffness in the joints and helps to improve recovery by training. This treatment is easy to use, affordable, non-invasive, and safe [ 17 ]. Intra-articular adhesions cause stiffness, as do peri-articular and intramuscular adhesions [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This therapy helps reduce pain in upper and lower extremities, edema and inflammation of soft tissue, muscle spasm, and subacute phases stiffness in the joints and helps to improve recovery by training. This treatment is easy to use, affordable, non-invasive, and safe [ 17 ]. Intra-articular adhesions cause stiffness, as do peri-articular and intramuscular adhesions [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contrast therapy has been utilized for several decades with good to excellent subjective and objective results reported. [1][2][3][4][5][6][7][8] This therapeutic approach has been advocated for patients with swelling (acute to chronic), pain, and loss of motion. In addition, contrast therapy has been utilized effectively for recovery post exercise and sport participation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, contrast therapy has been utilized effectively for recovery post exercise and sport participation. [1][2][3][4][5][6][7][8] Numerous studies have demonstrated excellent clinical effects with the performance of contrast therapy. [1][2][3][9][10][11] Greenhalgh et al 3 reported in a meta-analysis and systematic review utilizing contrast therapy in the management of both soft tissue injury and post exercise recovery beneficial effects for subjective measures such as fatigue, muscle soreness, and enhanced effects related to optimal recovery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the subacute period, contrast bath therapy (CB) is used to eliminate upper and lower limb pain, soft tissue inflammation, and edema, as well as muscle spasm and joint stiffness, and to aid recovery from training. It is a simple, safe, non-invasive, quick, and feasible musculoskeletal treatment option with a long history (8). Strengthening exercises improve OA knees in different ways, including increasing strength and improving psychological well-being (9).…”
Section: Introductionmentioning
confidence: 99%